Lad: a dog ebook - Terhune, Albert Payson (Sunnybank, 2012)
American author and respected dog breeder Albert Payson Terhune was so enamored of his handsome, loyal collie Lad that he was inspired to feature the furry fellow in a series of short stories. Originally published in magazines, the Lad stories became so popular that they took on a life of their own. Lad: A Dog , the first collection of Terhune's Lad tales, is sure to please dog lovers of all ages.